KONDISI SOSIAL EKONOMI MOBILISAN NON PERMANENDI KECAMATAN MAJALAYA KABUPATEN BANDUNG - Dena Rupi Handiani, - (2010)
The lack of infrastructure in village such as education, economical infrastructure, food and clothing center, even though tourism motivate villager to leave their home stay in order to move to big city. This movement is called , and the people who do that is called Mobilisan. Some of these terms, the main reason of people do population mobility is economic factor. People do Population mobility whether it is permanent or non-permanent the purpose is to their life better especially in their financial. According to that thing, the writer is interesting to do a research on "Non-Permanent MobilisanSocial Economic Condition In Majalaya Bandung Distric". In identify the problem, the writer making questions on this research. (1). How is the tendency of non-permanent population mobility system in Majalaya Bandung district? (2). what is the impact of population mobility to economic social condition of people who do Mobilisan in Majalaya Bandung district? To identify those problems, the writer use descriptive method. The sample zones of this study are taken from two villages, Majalaya and Majasetra Village, and sample of Mobilisan are 77 respondents. Technique used on sample zone is quota sampling meanwhile technique used on Mobilisan sample is accidental sampling. The analysis techniques' is percentage meanwhile to examine relation between variable the writer use statistic procedure theta (θ), gamma ( γ), and lambda (λ). From the analysis, the writer found that (1). Non-permanent population mobility in Majalaya Bandung district has a commutation pattern, it is because 70% respondents do non-permanent population mobility with commuting type. (2). Factors that influence economic social condition mobilisan in Majalaya such as gender influence kind of job, salary and life facility belonging. Age influence kind of job, salary, and life facility belonging. Education degree influence kind of job, salary and life facility belonging. The tendency of non-permanent population mobility system influence kind of job, salary and life facility belonging.